THE TERMINAL ORDOVICIAN EVENT AND PALEOZOOGEOGRAPHY OF BENTHIC AND PLANKTONIC FAUNAS (BRACHIOPODS AND GRAPTOLITES) - Koren T.N.; Popov L.E. (My University, 1996)
Climatic changes that resulted from the Late Ordovician glaciation coincided with the mass extinction and drastic alterations of the paleozoogeography of marine biota. The extinction of warm-water faunas in epicontinental seas, as well as some brachiopod assemblages on the open shelf at the beginning of the Hirnantian, apparently resulted from the glacio-eustatic regression and decrease of water temperature in low latitudes favored by the concentration of major continents in the southern hemisphere. The Hirnantian was a time when new paleozoogeographic relations were formed, which extended the distribution areas of short-lived cold-water faunas of the temperate belt, namely, of the Hirnantian brachiopod assemblage. After their extinction at the beginning of the Rhuddanian, the vacant ecologic space was occupied by impoverished assemblages of warm-water brachiopods, namely, virgianids and atrypids, which survived the biocoenotic crisis. With the advance of Llandoverian transgression, they occupied epicontinental seas and assumed a cosmopolitan character. The provincial differences of Graptoloidea were substantially obliterated before the initial Ashgillian. After the extinction event in the Hirnantian and reduction of black-shale sedimentation areas, the impoverished postcrisis diplograptid assemblages developed. The beginning of the adaptive radiation of graptolites corresponded to the end of the Hirnantian; however, its global effect was manifested later in the Rhuddanian, when Graptoloidea once again assumed planetary distribution areas.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская